Unexplained recurrent pregnancy loss: Novel causes and advanced treatment. (February 2023) - Yu, Na; Kwak-Kim, Joanne; Bao, Shihua
Abstract: In this study, recent research focusing on recurrent pregnancy loss (RPL) are reviewed. Recurrent pregnancy loss is a devastating reproductive health burden that affects about 5% of couples trying to conceive globally. Currently, there are few evidence-based diagnostic and treatment strategies for RPL. More so, the number of unexplained etiology cases in patients with RPL arrives at 50%. Here, we discuss the progress in diagnosis and treatment of unexplained RPL, as well as recommended treatment strategies and controversial etiologies. Highlights: Genetic abnormalities, mostly single nucleotide polymorphisms, are related to URPL. Single-cell RNA sequencing is utilized in discovery of new cell subgroups at the maternal-fetal interface. Lymphocyte immunotherapy may boost therapeutic effect in URPL patients. IVIG can improve the live birth rate of PRL patients with dysimmunity.